Complex Permittivity Determination of Glycerol Using Graphical and Numerical Technique - Syarifah Norsuhaila, Syed Mahmud; Mohamad Ashry, Jusoh; Kok, You Yeow; Fahmiruddin, Esa; Sutjipto, A. G. E. (AENSI Publishing, 2017)
Dielectric properties of materials are important parameters because these properties are related to other physical properties such as moisture content. The Cole –Cole model has been used successfully to describe the experimental data for the dielectric constant of many materials as a function of frequency. From Cole-Cole model, the value for dielectric constant divided into two, o= low limit frequency dielectric constant and = high limit frequency dielectric constant. Cole-Cole model also can determine the value for relaxation time of the material, This paper describes the dielectric constant and relaxation time determination of glycerol palm oil based using graphical and numerical methods. The value for dielectric constant was measured by glycerol produced using transesterification process of palm oil and measured at the ambient temperature. Cole-Cole model has been used todescribe the experimental data by using graphical and numerical methods. Using both methods, the value of dielectric constant and relaxation time can be determined by the data obtained from the experiment. Then identify the consistency of the dielectric constant and relaxation times obtained from both the methods were discussed. Dielectric measurement has been carried out to obtain experimental data of dielectric constant and relaxation time for glycerol palm oil based. From numerical method, the value for= 4.0, o= 47 and= 1.62 x10-10s. From graphical method, the value for = 4.0, o= 42.5and = 1.80 x10-10s. By comparing the result to previous research, both methods show a good approach to estimate the dielectric constant and relaxation time for glycerol palm oil based sample